Health-seeking trajectory of men with regards to symptoms of colorectal-cancer: A qualitative study - Oberoi, D.; Jiwa, M.; McManus, Alexandra; Hodder, R. (WILEY-BLACKWELL, 2014)
Background: Lower bowel symptoms are common, may impact on the health related quality of life (HRQoL) and predispose to colorectal cancer. Men have a higher risk of colorectal cancer (CRC) than women but are more likely to delay seeking medical advice for lower bowel symptoms. The current study provides an understanding of the barriers to consult a General Practitioner (GP) and of the trajectory of men’s health seeking between the onset of symptoms and diagnosis of CRC. Aim: This study seeks to explore the health-seeking trajectory of men experiencing lower bowel symptoms. Methods: In-depth semi-structured interviews were conducted among participants recruited via purposive sampling from three sub-groups: men experiencing lower bowel symptoms but never sought medical advice recruited from community (n=14), and men diagnosed with benign bowel conditions (n=19) and those with CRC (n=20) from tertiary care hospital. Interview data was audiotaped and transcribed verbatim and subsequently analyzed thematically. Andersen’s Model of Patient Delay was used as a theoretical framework.Results: The attribution of symptoms to benign conditions or to the participants' occupations, and the fear of cancer diagnosis were common barriers to health seeking across all groups of participants. The time and money needed to consult a GP and participants’ lack of trust in the medical system were other barriers among those who never sought advice. Some participants did not seek medical advice as the symptoms were intermittent or resolved spontaneously with changes in diet and lifestyle or with over the counter medication. Conclusions: The data highlights various reasons for delay in seeking medical advice for potential CRC symptoms among men. Barriers to health-seeking in primary care identified in this study may provide insight into more focused health-education and health-promotion campaigns for men with regards to timely diagnosis and treatment resulting in improved prognisis and HRQoL and reduced burden on hospital care.